2020
DOI: 10.3389/fpsyt.2020.00549
|View full text |Cite
|
Sign up to set email alerts
|

Complex Gastrointestinal and Endocrine Sources of Inflammation in Schizophrenia

Abstract: A low level, inflammatory phenotype is prevalent in individuals with schizophrenia, but the source of this inflammation is not known. Studies of the gut-brain axis indicate that this inflammation may be related to the translocation of intestinal microbes across a permeabilized gut-vasculature barrier. In addition, studies of the endocrine system support that this inflammation may derive from effects of stress hormones and metabolic imbalances. Gastrointestinal (GI) and endocrine conditions are not mutually exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Blood levels of LBP, sCD14 and NF κ B can reflect activity of this route. The group of Robert Yolken showed that these levels are increased in patients with BD and SSD, when patients had comorbid gastro-intestinal complaints (Severance et al, 2013 ; Severance, Dickerson, & Yolken, 2020 ). Moreover, Foster, Baker, and Dursun ( 2021 ) recently reviewed the relation of the GM and the immune system in MDD, where they draw attention to the importance of the immune system as an important player in the neurobiology combined with the GM in subtypes of depression.…”
Section: Gut–brain Axismentioning
confidence: 99%
“…Blood levels of LBP, sCD14 and NF κ B can reflect activity of this route. The group of Robert Yolken showed that these levels are increased in patients with BD and SSD, when patients had comorbid gastro-intestinal complaints (Severance et al, 2013 ; Severance, Dickerson, & Yolken, 2020 ). Moreover, Foster, Baker, and Dursun ( 2021 ) recently reviewed the relation of the GM and the immune system in MDD, where they draw attention to the importance of the immune system as an important player in the neurobiology combined with the GM in subtypes of depression.…”
Section: Gut–brain Axismentioning
confidence: 99%
“…Moreover, altered levels of antigliadin and anti- Saccharomyces cerevisiae antibodies have been reported in patients with schizophrenia and FEP [32]. Finally, the levels of various immune-inflammatory markers have been associated with gastrointestinal diseases in patients with schizophrenia [33].…”
Section: Evidence From Human Studiesmentioning
confidence: 99%
“…Recent studies on correlations between gut dysbiosis and psychiatric diseases have noted a strong connection between SCZ and altered gut microbiota [ 81 , 85 , 86 ]. A central concept arising from several reviewed studies investigating the gut microbiota-SCZ relationship is that the gut microbiota is a crucial factor in the early life development and neural maturation, including immune and endocrine systems [ 87 90 ]. These physio-behavioral processes are frequently impaired in SCZ patients.…”
Section: Gut Microbiotamentioning
confidence: 99%